FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA KEUANGAN PERUSAHAAN PROPERTY DAN REAL ESTATE - Giovani , Tabita; Surjadi, Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This exploration aims to gain empirical substantiation about the effect of profitability, influence, liquidity, and company size on company fiscal performance during 2019- 2021. This study used an intentional slice system with a total sample of 30 property and real estate companies. Data recycling in this study uses multiple retrogression analysis ways with the help of the Eviews 12 SV and Microsoft Excel 2021 programs. The results of this study indicate that profitability and establishment size have a significant positive effect on fiscal performance, influence has a significant negative effect on fiscal performance, and liquidity has no influence on fiscal performance. The recrimination of this exploration is the need to pay attention to financial statements and the size of a company to ameliorate fiscal performance with the end of achieving success pretensions and being a good signal for investors.